2021
DOI: 10.21203/rs.3.rs-368807/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is the Health-Awareness of Leaders Related to the Working Conditions, Engagement, and Exhaustion in Their Teams? A Multi-Level Mediation Study.

Abstract: Background: Research shows that leaders influence the health and well-being of employees, by being either a buffer or major source of employee's work stressors. Various leadership behaviors and their relation to employee outcomes have been examined. Yet, a satisfactory explanation of how leaders’ behavior influences health has not been found. A new line of research investigates the construct of “health-oriented leadership”, that is, the health awareness of leaders towards themselves (“self-care”) and towards t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Health awareness of leaders is as important as staff care, as it has implications for behavior change. A study by Grimm et al (2021) found that the stronger a leader's health-orientation toward self-care, the stronger their health-orientation toward their employees. The principal's focus on self-development plays a crucial role in successful leadership (Steyn, 2014), and the same can be said for HPL.…”
Section: Discussionmentioning
confidence: 99%
“…Health awareness of leaders is as important as staff care, as it has implications for behavior change. A study by Grimm et al (2021) found that the stronger a leader's health-orientation toward self-care, the stronger their health-orientation toward their employees. The principal's focus on self-development plays a crucial role in successful leadership (Steyn, 2014), and the same can be said for HPL.…”
Section: Discussionmentioning
confidence: 99%